Short-chain fatty acids induced lung tumor cell death and increased peripheral blood CD4+ T cells in NSCLC and control patients ex vivo - Thome, Carolin D.; Tausche, Patrick; Hohenberger, Katja; Yang, Zuqin; Krammer, Susanne; Trufa, Denis I.; Sirbu, Horia; Schmidt, Joachim; Finotto, Susetta (Frontiers in Immunology, 2024)
This study focuses on the impact of the short-chain fatty acid (SCFA) Sodium Butyrate (SB), on lung cancer cell survival. We previously described a pro-tumoral role of glucose on A549 lung adenocarcinoma cell line. In this study, we wanted to know if SB would counteract the effect of glucose and thus cultured A549 and H520 in vitro with and without SB in the presence or absence of glucose and investigated how the treatment with SB affects the survival of lung cancer cells and its influence on immune cells fighting against lung cancer. To investigate the effect of SB on lung tumor cells, we first analyzed the effect of 6 different concentrations of SB on A549 cells at 48 and 72 hours cell culture. Here we found that, SB treatment reduced lung cancer cell survival in a concentration dependent manner. We next focused our deeper analysis on the two concentrations, which caused the maximal reduction in cell survival. Here, we observed that SB led to cell cycle arrest and induced early apoptosis in A549 lung cancer cells. The expression of cell cycle regulatory proteins and A549 lung cancer stem cell markers (CD90) was induced. Additionally, this study explored the role of interferon-gamma (IFN-γ) and its receptor (IFN-γ-R1) in combination with SB treatment, revealing that, although IFN-γ-R1 expression was increased, IFN-γ did not affect the efficacy of SB in reducing tumor cell viability. Furthermore, we examined the effects of SB on immune cells, specifically CD8+ T cells and natural killer (NK) cells from healthy individuals, smokers, and NSCLC patients. SB treatment resulted in a decreased production of IFN-γ and granzyme B in CD8+ T cells and NK cells. Moreover, SB induced IFN-γ-R1 in NK cells and CD4+ T cells in the absence of glucose both in PBMCs from controls and NSCLC subjects. Overall, this study highlights the potential of SB in inhibiting lung cancer cell growth, triggering apoptosis, inducing cell cycle arrest, and modulating immune responses by activating peripheral blood CD4+ T cells while selectively inducing IFN-γ-R1 in NK cells in peripheral blood and inhibiting peripheral blood CD8+ and NK+ T cells.